Atypical Polypoid Adenomyoma of the Vagina: Follow Up and Subsequent Evolution: A Case Report and Update - Melinda Ildiko Mitranovici; Ioan Emilian Oală; Izabella Petre; Marius Lucian Craina; Silviana Narcisa Floruț; Diana Maria Chiorean; Iuliu Gabriel Cocuz; Sabin Gligore Turdean; Ovidiu Simion Cotoi; Lucian Pușcașiu (Diagnostics, 2022)
Atypical polypoid adenomyoma (APA) is a rare tumor developed from a mix of cells of epithelial and mesenchymal origin. We present the case of an 84-year-old patient with atypical polypoid adenomyoma on the vaginal vault, after total hysterectomy with total adnexectomy for endometrial hyperplasia with atypia four years ago. Not following regular indicated gynecological appointments, the symptoms presented were vaginal bleeding and anemia. The importance of the case consists both in the unique way in which the adenomyoma appears on the vaginal vault and in the subsequent evolution of this pathology. After complete resection, it recurs in five months with a malignant transformation into carcinosarcoma. This fact shows that adenomas can turn not only into carcinomas but also the mesenchymal component can progress to sarcoma, a fact of exceptional rarity. Follow-up and accurate diagnosis are essential for proper management, which is a challenge anyway due to the lack of case studies.